Technological Adaptation, Cities, and New Work - Lin, Jeffrey (The Review of Economics and Statistics, 2011)
Where does adaptation to innovation take place? I present evidence on the role of agglomeration economies in the application of new knowledge to production. All else equal, workers are more likely to be observed in new work in locations initially dense in college graduates and industry variety. This pattern is consistent with economies from the geographic concentration of factors and markets related to technological adaptation. A main contribution is a new measure, based on revisions to occupation classifications, that characterizes cross-sectional differences across cities in technological adaptation. Worker-level results also provide new evidence on the skill bias of recent innovations.